Measurement of salinity in slurry based on modified electrical conductivity method. (29th April 2021) - Yuan, Jing; Zhang, Minxi; Yu, Guoliang
Abstract: Salinity is an important factor in the management of inland and oceanic water resources. Currently, the electrical conductivity (EC) method is widely used for the measurement of salinity in different components of the environment. However, this method is not reliable for the measurement of salinity in slurry, as the conversion formula from the EC value to salinity does not consider fine particle size and its content. In this study, the salinity of slurry based on EC measurements was extensively investigated. In total, 1148 laboratory tests and 40 field tests were performed. The results indicate that the EC value is mainly influenced by the salinity, temperature, fine particle size, fine particle content, and sediment concentration of slurry. The fine particle size and its content play an important role in the measurement of salinity in slurry. The surface coefficient of the fine particles was herein considered as the parameter to indicate the effects of fine particle size and its content on the EC value. The results show that the effects of salinity and temperature on the EC measurement are more significant than that of the surface coefficient of fine particles and sediment concentration. Although the EC of slurry is positively and linearly related to salinity and temperature, it has negative relationships with the surface coefficient of fine particles and sediment concentration. Based on dimensional analysis and experimental data, a new formula was proposed for the calculation of salinity which considers the EC, sediment concentration, surface coefficient of fine particles, and temperature of the slurry. This modified conversion formula for the EC method was successfully tested with laboratory, field and other scholars' data, which assures a reliable salinity measurement of slurry in shallow oligohaline water areas.